DEMAND MANAGEMENT AND PRODUCTION CAPACITY IN SERVICE SECTOR MSMEs IN BATAM CITY - Dewi, Elinda Nurul Hasana B. S.; Depari, Irene Juwita; Pramita, Nina; Syafrina, Intania; Haryanto, Hery (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study aims to find out what methods Irepairgo MSMEs use in accepting the request process, how Irepairgo MSMEs in handling service requests that increase in a period to remain effective and timely, Irepairgo MSMEs demand patterns, and the advantages of Irepairgo MSMEs from other MSMEs. This research uses qualitative methods by using several interview and observation techniques. The results showed that the performance of the iRepair Go MSMEs compared to the iRepairgo MSMEs increased in the second quarter of each year. It can be seen from the demand graph for services from iRepairgo appears to have increased and improved from the 3rd quarter of 2020 to the 2nd quarter of 2021 before experiencing a slight decline again in the 3rd quarter of 2021 and rising again in the 4th quarter of 2021. It is also suspected that demand was helped to rise after consumers and enthusiasts of products from Apple were able to get the Apple products they wanted through the iBox online store (PT. Data Citra Mandiri), which is one of the licensees as the first distributor of Apple products in Indonesia, and was then followed by one of the subsidiary of PT. Mitra Adiperkasa Tbk (MAP group), namely Digimap, which is also the official distributor of Apple products.